Reconstruction of Tolaki and Moronene Language Vocal Protophonemes - Wawan Marhanjono Mustamar; Aron Meko Mbete; Ni Made Dhanawaty; I Gede Budasi (The Doctoral Studies Program of Linguistics of Udayana University, 2019)
The Tolaki language and the Moronene languages are part of the Austronesianlanguage group. The reconstruction is done based on the hypothesis of a genetic relationship andregularity. Historical comparison methods were used in this study. The purpose of thereconstruction was to obtain accurate results on the assessment of language relations. It isdeemed necessary to reconstruct the proto in order to seek the evidence of the retention andinnovation that occur in the two respective languages. From the reconstruction, several findingsand proofs were generated, which among others are TlM vocal proto-phonemes: *a, *i, *u, *e,and *o; PTlMr *a are found at the beginning, middle and the end of the word. The proto-phonemes are 1) *a (a-, -a-, -a)> Tl, Mr a, 2) PTlMr *i (i- -i- -i)> Tl, Mr i, 3) PTlMr *u (u -, -u-, -u)> Tl, Mr u, 4) PTlMr *e (e-, -e-, e-)> Tl, Mr e, and 5) PTlMr *o (o-, -o-, o-)> Tl Mr o.